Singing for the dead, on and off line: Diversity, migration, and scale in Mexican Muertos music. (September 2015) - Faudree, Paja
Abstract: This article examines the recent emergence of online debates about Day of the Dead music, one of countless sites worldwide where conversations about diversity take place in the shadow of state policies. There, people engage diversity not through the state-centric "managerial discourse" of "diversity talk" but through localized interpretations of sameness and difference. I discuss the social effects of semiotic processes through which people consider sameness and difference: the emergence of a regional venue for debating contentious issues and the consolidation of an implicit consensus of linguistic practice. Attending to local understandings of difference can reduce the risk of taking state-sponsored views of (linguistic) diversity as natural kinds while recovering diversity and surrounding ideologies as ethnographic objects. Highlights: "Diversity talk" is a specific, powerful speech genre where sameness and difference are constructed. Understanding sameness and difference requires considering their meaning apart from state policy. This article looks for such meaning in vernacular talk: here, debates about "traditional" music. Stressing vernacular meanings can reduce the risk of taking state views of diversity for granted.